Characteristics of atmospheric compositions in the background area of Yangtze River delta during heavy air pollution episode - Xu, Hong-Hui; Pu, Jing-Jiao; He, Jun; Liu, Jie; Qi, Bing; Du, Rong-Guang (Hindawi Publishing Corporation, 2016)
In order to understand the formation and evolution of recurrent severe haze pollution episodes in Yangtze River Delta, China, a short comparative sampling campaign was conducted at the Lin’an background monitoring station from 25 November 2013 to 14 December 2013. The characteristic concentrations of PM2.5, black carbon, CO2, CO, and CH4 have been systematically recorded at the abovementioned site. Coupled with detailed analysis of air backward trajectories, fire spot distribution surrounding the studied site and meteorological impacts, temporal trend, diurnal variation, and intercorrelation of the aforementioned species have also been comprehensively investigated throughout prehaze, haze, and posthaze periods.